Photography and architecture in the modern age - Pardo, Alona (New York Prestel, 2014)
Architecture has long been a subject matter for photographers, who utilise the medium not just to document the built world, but also to reveal wider truths about society. This book features chapters devoted to various artists - among them, Berenice Abbott, Walker Evans, Ed Ruscha, Bernd and Hilla Becher, Andreas Gursky and Iwan Baan - and includes 220 colour and duotone images. Each chapter opens with a text introducing the artists' work, followed by reproductions of their photographs. Arranged chronologically, the book documents the birth of the skyscraper against the backdrop of the Great Depression; the rise of the modernist tradition in America, post-colonial Africa, and India; the effects of industry on 1960s Europe; the increasing suburbanization of America and Europe; and the consequences of today's mass urbanization in Asia, the Middle East and South America. Far-reaching and penetrating, this volume reflects on the on-going dialogue between photography and architecture. This book also contains a contextualising essay by curators Alona Pardo and Elias Redstone and a history of the relationship between photography and architecture written by David Campany, Published in association with the Barbican Art Gallery, London.
Keywords: PHOTOGRAPHY (AR-PHO)